DAMPAK PENDIDIKAN LIFE SKILL PADA MASYARAKAT MARGINAL: Studi Kasus: Pendidikan Life Skill di Sanggar Ciliwung Merdeka,Bukit Duri, Jakarta Selatan - Purnamasari, Fiky (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2018)
This research using a qualitative approach to data get a deeper by digging to informants research. Source of the data obtained by using observations, observation involved, interview, documentation and the study of literature. Data collected from September 2015 until April 2016. Data analysis used in processing the data consisting of the reduction of the data, display data or presentation of data, and withdrawal of the conclusions. The results showed that in learning had been conducted three aspects from of planning, implementation, and evaluation. The process has worked very well so as to produce the purpose of education life skill expected. In addition, the impact of seen by researchers during the survey last the economic impact seen economic development of life lessons skill at Sanggar Ciliwung Merdeka. The impact of education seen the result of learning life skill at Sanggar Ciliwung Merdeka produce students can use of the study by means of into teaching at sanggar or regular public schools. The impact of social interaction seen social relations more positive of life lessons skill at Sanggar Ciliwung Merdeka. This evident from the community cooperation marginal Bukit Duri and the sanggar to make the public market which aims to refuse eviction and strengthen relationship between residents.